Habilidade de cuidado de cuidadores familiares de pacientes em tratamento oncológico e sua relação com a sobrecarga, estresse e coping - Coppetti, Larissa de Carli (2018)
This study aims to evaluate the relationship of care ability with stress, coping strategies and coping strategies of the family caregiver of patients on cancer treatment. This is a cross-sectional study carried out with 132 family caregivers with the use of a demographic and clinical questionnaire for the patients, a sociodemographic questionnaire of the caregivers and characteristics of the care, the Brazilian version of Caring Ability Inventory, the Zarit Overload Scale, the Perceived Stress Scale, and COPE Brief.The qualitative variables were presented by the distribution of absolute and relative frequencies and the quantitative variables in measures of central tendency and variability. Spearman's Correlation, Student's t-Test, Mann-Whitney or Kruskal-Wallis, according to the distribution of the data, were performed at significance level ≤5%. Prevalence of male patients, mean age of 66.52 years, with cancer of the digestive tract and moderate dependence was observed.The majority of the caregivers were women, with a mean age of 48.68 years, with a partner, with a low level of schooling, with an average time of care of 10.18 months, who did not perform paid work at the time and received care assistance.There was a mean level of total ability (67.42%) and knowledge (65.91%), courage (68.94%) and patience (75.76%). As for the overload, 49.2% presented mild to moderate overload. The majority of caregivers presented medium level of stress (46.21%) and coping strategies focused on the problem. Among established associations, total care ability was significantly associated with the patient's age, schooling and marital status of the caregiver, overload in the interpersonal relationship factor, stress, problem focused coping, and emotionally focused maladaptive coping. The knowledge dimension has demonstrated association with stress, problem- focused coping, and adaptive focused on emotion. In the courage dimension, we observed a significant association with the patient's age, caregiver education, overload on self-efficacy perception and interpersonal relationship, stress and maladaptive coping focused on emotion. The patience dimension was associated with the patient's age, schooling, and the caregiver's marital status and length of care. Significant association of the overload with the degree of dependence of the patient, the age of the caregiver and the assistance of third parties were observed. It was concluded that there is an association between the care ability and the clinical characteristics of the patients in oncological treatment, the sociodemographic characteristics of the caregivers, the characteristics of the care provided by them, the overload, stress and coping of the family caregivers. It should be emphasized that the promotion of support and guidance provided by nursing professionals with a view to preparing family caregivers for home care may contribute to minimize the occurrence of overload and stress, as well as the adoption of effective coping strategies, so that these factors do not negatively interfere with their ability to care.